Metallization and superconductivity of NBH12 compounds stabilized by dihydrogen bonds. Issue 8 (26th January 2022) - Shi, Lan-Ting; Turnbull, Robin; Liang, Akun; Chen, Xiang-Rong; Ji, Guang-Fu
Abstract : As the most promising hydrogen storage material, ammonia borane (NH3 BH3, AB) has been the subject of study in a variety of scientific fields. Abstract : As the most promising hydrogen storage material, ammonia borane (NH3 BH3, AB) has been the subject of study in a variety of scientific fields. Here, we predict for the first time that the hydrogen storage capacity of AB can be increased from 19.6 wt% up to 32.8 wt% via insertion of H2 molecules into its crystal structure. We present particle swarm optimization algorithms combined with density functional theory calculations which predicted a new hydrogen-rich phase of AB in which AB and H2 have a ratio of 1 : 3. The new phase, AB–(H2 )3, is stable over a wide pressure range from 20–240 GPa. Interestingly, the AB–(H2 )3 crystal structure maintains the same P 21 space-group symmetry as pure AB and the inserted hydrogen molecules are located between the layers of ammonia borane molecules, thereby introducing a network of dihydrogen bonds between ammonia borane and hydrogen molecules which greatly stabilizes the structure and reduces the metallization pressure of AB from 600 GPa to 240 GPa. The calculated electronic properties show that the electronic band gap of P 21 -AB(H2 )3 gradually closes with increasing pressure, finally reaching a semi-metallic state at about 240 GPa. Surprisingly, the electron–phonon coupling calculations show that P 21 -AB(H2 )3 exhibits superconductivity after metallization (at 240 GPa and 12 K) which is primarily attributed to acoustic phonon mode softening. This study provides insights into hydrogen storage materials with increased storage capacity under high pressure conditions, and it also provides new directions for the synthesis of covalent hydrogen-rich compounds.